2008
DOI: 10.3741/jkwra.2008.41.12.1231
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Runoff Curve Number for Chungju Dam Watershed Using SWAT

Abstract: The objective of this study is to present a methodology for estimating runoff curve number(CN) using SWAT model which is capable of reflecting watershed heterogeneity such as climate condition, land use, soil type. The proposed CN estimation method is based on the asymptotic CN method and particularly, it uses surface flow data simulated by SWAT. This method has advantages to estimate spatial CN values according to subbasin division and to reflect watershed characteristics because the calibration process has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Particularly for rainfall events of less than 10 mm, the estimated CN values were greater than 90 in most land cover types except those for uplands and orchards. This result might be caused by the value for S (potential maximum retention after runoff begins), which is largely affected by high runoff occurring from high rainfall events (Kim et al , ; Kwak et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly for rainfall events of less than 10 mm, the estimated CN values were greater than 90 in most land cover types except those for uplands and orchards. This result might be caused by the value for S (potential maximum retention after runoff begins), which is largely affected by high runoff occurring from high rainfall events (Kim et al , ; Kwak et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…These application studies showed that there is an asymptotic relationship between CN and rainfall amounts. Also, Kim et al () and Kwak et al () illustrated that direct runoff estimated using the ACN‐RB method matched observed runoff better than estimates using the original NRCS‐CN method did.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…연구지역의 주요 지질은 하부 로부터 계명산층, 향산리돌로마이트층, 대향산규암층, 문 주리층, 운교리층, 황강리층 등과 이를 관입한 중생대 화 성암류로 구성된다. 화성암류는 주로 조립질반상화강암, 흑운모화강암, 각섬석화강암, 화강반암, 규장암, 염기성암 맥, 산성암류 등으로 이루어져 있다 (Kim and Lee, 1965;Lee and Kim, 1972). 또한 연구지역의 지질을 구성하는 변성암류는 변성이질암, 화강암질편마암, 함철규암, 변성 심성산성암, 변성반심성산성암, 변성화산산성암, 변성염 기성암, 변성역질암, 변성사질암, 규암, 결정질 돌로마이 트질석회암 등으로 구성되어 있다 (Kang et al, 2017).…”
Section: 연구지역 및 지질개요unclassified
“…, 특히 Cho et al (2004) and Kim et al (2007) (Park et al, 2005;Lee et al, 2005 (Mogeln, 2000;Paudel et al, 2009;Ebrahimian et al, 2012;Moon et al, 2014 6 2006, 2007, 2008, 2009, 2010 6 2006, 2007, 2008, 2009, 2010 3 2005, 2006, 2007, 2008, 2009, 2010 7 2006, 2007, 2008, 2009, 2010, 2011Cheongju Geum River 161.44 32.84 20.1 2006, 2007, 2008, 2009, 2010, 2011 Chunyang Youngsan River 143.1 16.74 34.3 2006, 2007, 2008, 2009Toigyewon Han River 200.45 27.92 26.7 2005, 2006, 2007, 2008, 2009, 2010, 2011Pyeongchang Han River 695.67 72.84 40.3 2005, 2006, 2007, 2008, 2009, 2010, 2011...…”
mentioning
confidence: 98%